Self-lubricating, dirt-resistant spandex and preparation method thereof
By introducing silicon oxygen bonds and fluorine atoms into spandex fibers and using fluorine siliconization chemical modification method, the self-lubricating and dirt resistance of spandex is achieved, and the poor unwinding and easy pollution in the production and use of existing spandex fibers are solved. The problem of accumulation significantly improves mechanical properties and comfort.
Patent Information
- Application Number
- CN202411553906.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-04
AI Technical Summary
During the production and use of existing spandex fibers, due to high friction coefficient, easy adhesion and adsorption of dirt, resulting in poor unwinding, low production efficiency and increased cost. Traditional lubricants affect the mechanical properties and hot melt bonding effect.
By introducing silicon oxygen bonds into the main chain of spandex and introducing fluorine atoms into the side chain, the fluorosilication chemical modification method is used to achieve the self-lubricating and dirt resistance of spandex without the need for external lubricant.
The surface friction coefficient of spandex fiber is significantly reduced, the unwinding and dirt resistance are improved, the mechanical properties and comfort of use are enhanced, and the contradiction between lubricity and mechanical properties is solved.
Smart Images

Figure CN119041052B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of spandex fiber manufacturing, and in particular to self-lubricating, dirt-resistant spandex and a preparation method thereof. Background Art
[0002] Spandex is an elastic fiber with polyurethane as its main structure. It has the characteristics of high elongation, good resilience, skin-friendly and comfortable. Only a small amount of it needs to be added to textile fabrics to significantly improve the shape retention, drape and wrinkle resistance of clothing, giving the clothing an overall beautiful shape. Therefore, spandex is known as "human's second skin" and "MSG fiber". It has been widely used in various fields such as textiles and clothing, stockings, home textiles, medical consumables, and sanitary materials.
[0003] At present, the production technology of spandex spinning shows a trend of multi-head and rapid development, with the highest spinning speed reaching more than 1000m / min. When spandex products are used in downstream textile equipment, the speed of use also reaches hundreds of kilometers per minute, so the requirements for spandex products are also constantly increasing: on the one hand, the surface friction coefficient of spandex yarn is required to be low, which is conducive to the rapid winding and forming on the guide roller and winding equipment during the spinning production process, without breaking the yarn and good spinning continuity; on the other hand, the spandex yarn made by winding needs to have good unwinding performance when used downstream. If the unwinding is not smooth and causes the yarn to break and cause downtime, it will directly lead to reduced textile production efficiency, increased costs, and affect customer experience.
[0004] However, the main properties of spandex are similar to those of rubber elastomers, with a high friction coefficient. If it is left for a long time or the temperature of the transportation environment is too high, the filaments are easy to stick together, making the unwinding property worse. The friction will generate static electricity and easily absorb dirt. All of the above unfavorable factors will seriously affect the effect of spandex during production and use.
[0005] In the existing technology, in order to solve the above problems, the most common method is to attach a layer of spinning oil to the surface of spandex through an oil roller or an oil nozzle during the production process of spandex spinning, so as to reduce the surface friction coefficient and enhance the surface lubricity, thereby improving the spinning continuity and unwinding performance. However, the oil attached to the surface is very easy to be contaminated with dirt, dust and other impurities, and in some application fields involving hot melt bonding of spandex yarn and different textile fabrics, the oil will act as a barrier layer to affect the hot melt bonding effect. If the oil content is reduced or no oil is applied on this basis, it is easy to cause the surface friction of the spandex yarn to be large and the astringency to be obvious, which is not conducive to spinning production and unwinding use, and has difficult to resolve contradictions. Some existing technologies add lubricant components to the spandex stock solution during the polymerization process to achieve lubrication effect and good unwinding performance, but since the main properties of spandex have not changed, the dirt resistance has not been significantly improved.
[0006] CN115449904B discloses a method for preparing spandex for sanitary materials with excellent unwinding performance, which comprises first mixing the polymer microspheres with an organic solvent, adding a nonionic surfactant and using ultrasonic oscillation technology to form a uniform polymer microsphere dispersion, then mixing the polymer microsphere dispersion with a polyurethane solution to obtain a spinning solution; after filtering the spinning solution, the organic solvent is removed by evaporation through a high-temperature channel to form nascent fibers; then the nascent fibers are subjected to false twisting and cold oil treatment to finally obtain spandex for sanitary materials. Since the polymer microspheres can form arc-shaped convex structures on the surface of the spandex fibers, the contact area between the fibers can be reduced and the formation of adhesion can be alleviated; the unique self-lubricating effect of the polymer microspheres is utilized to make the fibers still have good mutual isolation under the condition of low oil content, thereby ensuring that the silk rolls can be completely and smoothly unwound from the outside to the inside.
[0007] CN102362020B discloses an elastic fiber containing an anti-sticking additive. Different types of cellulose (such as cellulose butyrate, cellulose acetate butyrate, cellulose acetate propionate and mixtures thereof) are used as soluble anti-sticking agents. 0.5 wt % to 25 wt % are added to a polyurethane or polyurethane urea matrix, and spandex is made through a spinning process, thereby reducing the surface viscosity of the spandex yarn and improving the unwinding property of the spandex yarn.
[0008] CN113005559B discloses a method for preparing nano-modified easy-to-unwind spandex, wherein nano-particles such as molybdenum disulfide, diamond powder, and UDP are prepared into a dispersion as a lubricating functional additive, which is added into a polyurethane urea solution and stirred to form a spinning solution, which is then dry-spun into spandex fibers. The higher the content of the nano-lubricating functional additive, the better the fiber unwinding property, thereby solving the problems of unwinding breakage and easy adhesion in subsequent use.
[0009] CN108221076B discloses a method for preparing spandex for diapers, wherein polyhedral oligomeric silsesquioxane (POSS) is added to a polyurethane urea solution and mixed and matured to obtain a spinning solution, which is then made into spandex by dry spinning. The method can improve the problems of high friction coefficient on the fiber surface, poor unwinding, easy adhesion, easy breakage of the fiber, etc. without oiling, and has good adhesion with sanitary materials.
[0010] The solid lubricants in the above prior art usually need to be added in large quantities to achieve an effective lubricating effect on the fiber surface, which will affect the continuity of the fiber matrix and lead to a decrease in mechanical properties. Due to the small particle size and high surface energy of solid lubricants, solid lubricant particles are very easy to agglomerate on the fiber surface or during the spinning process. The agglomerated particles are difficult to form a uniform lubricating layer on the fiber surface, resulting in poor uniformity of the product strips made during spinning production, and the probability of broken wires during production and use increases, which directly affects the continuity and mechanical properties of the fiber. Liquid lubricants are difficult to mix evenly due to their large differences in chemical structure characteristics with the polyurethane matrix, poor compatibility, and are difficult to mix evenly. Phase separation is prone to occur during the polymerization production process, resulting in an unstable stock liquid state, which directly affects the spinning production; and during the later use or storage of the finished silk, the liquid lubricant is easy to migrate and precipitate, and the mechanical properties deteriorate, and it cannot play its original role.
[0011] CN111155313B discloses a modified spandex fiber material and a preparation method thereof, wherein the spandex fiber surface is first pretreated with isocyanate, and then subjected to a grafting reaction with a polyamino compound, and then metal ions are adsorbed as active sites, followed by a sulfur ion reaction, and then further grafted with a fluorinated silicon reagent, and finally fluorinated silicon side chains are grafted onto the spandex fiber surface to impart a self-cleaning effect to the surface. However, due to the cumbersome reaction steps, the effective grafting rate of the fluorinated silicon side chains is very low, and due to the distribution of active sites, the fluorinated silicon functional side chains are difficult to be evenly distributed and fully covered. Although the modified spandex product prepared by the technical solution has certain water and oil repellency properties, it is limited by the low grafting efficiency and uneven distribution of the fluorinated silicon reagent, and the anti-fouling effect is not ideal, and the surface friction coefficient is basically not improved.
[0012] Therefore, the various technologies for improving the surface lubricity and stain resistance of spandex in the above-mentioned prior art still have shortcomings and deficiencies, which is a problem that needs to be solved urgently in the current technology. Summary of the invention
[0013] In view of the problems existing in the prior art, the present invention provides a self-lubricating and dirt-resistant spandex and a preparation method. The present invention introduces silicon-oxygen bonds into the main chain of the spandex through chemical modification, and at the same time forms a group containing fluorine atoms in the side chain, which not only gives the spandex fiber excellent self-lubricating properties, greatly reduces the surface friction coefficient, but also enables it to have excellent dirt resistance. By optimizing the chemical structure of the spandex matrix, the present application does not need to rely on externally added lubricants or oils, and fundamentally solves the dilemma of the traditional spandex that is difficult to reconcile between lubricity and mechanical properties. The spandex products produced have good comprehensive mechanical properties.
[0014] The technical solution of the present invention is as follows:
[0015] The present invention provides a self-lubricating, dirt-resistant spandex, wherein the number average molecular weight of the self-lubricating, dirt-resistant spandex is 30,000-50,000 g / mol, the main chain of the molecular structure contains a silicon-oxygen bond, and the side chain contains a fluorine atom. The molecular structure of the self-lubricating, dirt-resistant spandex comprises the following general formula (I):
[0016] ;
[0017] Formula (I)
[0018] Among them, R1 is ;
[0019] R2 is ;
[0020] a, b, c, x and y are all positive integers;
[0021] a=3~13, b=2~27, c=2~20;
[0022] x is the degree of polymerization of the soft segment, x=57~108;
[0023] y is the degree of polymerization of the hard segment, y=33~78.
[0024] Furthermore, the friction coefficient of the self-lubricating and stain-resistant spandex is 0.164-0.221, the breaking strength is 1.15-1.44 cN / dtex, the breaking elongation is 594.6-786.5%, the 300% elongation rebound is 94.2-96.2%, and the unevenness is 1.4-1.8%.
[0025] Furthermore, the liquid dirt residue of the self-lubricating and dirt-resistant spandex is 3.3-7.8wt%, and the solid dirt residue is 1.5-2.1wt%.
[0026] Furthermore, the unwinding tension of the self-lubricating and stain-resistant spandex is 1.01-1.55 cN.
[0027] The present invention also provides a method for preparing the self-lubricating, dirt-resistant spandex. The reaction equation is as follows: Figure 2 As shown, the following steps are included:
[0028] Step S1 Prepolymerization reaction:
[0029] 4,4'-diphenylmethane diisocyanate and fluorinated siliconized modified polyether diol are subjected to prepolymerization reaction to form isocyanate terminated fluorinated siliconized modified polyurethane prepolymer, and N,N'-dimethylacetamide is added to dissolve the prepolymer to prepare a fluorinated siliconized modified polyurethane prepolymer solution;
[0030] Step S2 Chain extension reaction:
[0031] Adding a mixed amine solution consisting of a fluorine-modified amine chain extender, 1,2-propylenediamine, diethylamine, and N,N'-dimethylacetamide to the fluorine-siliconized modified polyurethane prepolymer solution to carry out a chain extension reaction to form a fluorine-siliconized modified polyurethane urea solution, and preparing a spinning solution by adding auxiliary materials, stirring, and aging;
[0032] Step S3 Spinning:
[0033] The spinning solution is filtered and degassed before being dry-spun, and then false-twisted and wound to obtain self-lubricating and dirt-resistant spandex without oiling.
[0034] Furthermore, in step S1, the number average molecular weight of the fluorinated siliconized modified polyether diol is 1000-4000 g / mol.
[0035] Further, in step S1, the fluorosilicified modified polyether diol is prepared by ring-opening reaction with ethylene oxide (EO) and propylene oxide (PO) in sequence using terminal hydroxyl poly (methyl-3,3,3-trifluoropropyl) siloxane with a number average molecular weight of 500-2000 g / mol as an initiator, wherein the mass ratio of EO segment to PO segment is (0.5-2):1, and the reaction equation is as follows:
[0036] ;
[0037] Where a, b, and c are the polymerization degrees of the siloxane segment, EO segment, and PO segment, respectively; a=3~13, b=2~27, and c=2~20.
[0038] Furthermore, the ring-opening reaction is prepared by reacting the terminal hydroxyl poly(methyl-3,3,3-trifluoropropyl)siloxane with ethylene oxide and propylene oxide in sequence for 2 to 5 hours at a temperature of 50 to 70°C using Lewis acid as a catalyst.
[0039] Furthermore, in step S1, the molar ratio of the 4,4'-diphenylmethane diisocyanate to the fluorinated siliconized modified polyether diol is (1.5-3):1.
[0040] Furthermore, in step S1, the temperature of the prepolymerization reaction is 50-80° C., and the reaction time is 60-120 min.
[0041] Further, in step S2, the fluorine-modified amine chain extender is prepared by Michael addition reaction of ethylenediamine and trifluoroethyl acrylate, as shown in the following figure:
[0042]
[0043] Furthermore, the Michael addition reaction is prepared by reacting ethylenediamine and trifluoroethyl acrylate in a molar ratio of 1:1 at a temperature of 60-80° C. for 4-8 hours.
[0044] Furthermore, in step S2, the molar ratio of the fluorine-modified amine chain extender, 1,2-propylenediamine, and diethylamine is (5.4-10.8): (0.6-1.2):1.
[0045] Furthermore, in step S2, the mass ratio of the fluorinated siliconized modified polyurethane prepolymer solution to the mixed amine solution is (1.88-2.69):1.
[0046] Furthermore, in step S2, diethylamine is added as a terminator in the chain extension reaction, the function of which is to prevent the viscosity of the polymerization stock solution from increasing too fast.
[0047] Furthermore, in step S2, the temperature of the chain extension reaction is 30-50° C., and the reaction time is 40 min-80 min.
[0048] Furthermore, in step S2, the auxiliary material is one or more of an antioxidant, an anti-yellowing agent, and a matting agent.
[0049] Furthermore, the amount of the auxiliary material is 2-5% of the solid content of the spandex matrix; the specific amounts of the antioxidant, anti-yellowing agent and matting agent can be flexibly adjusted according to the requirements of the spandex appearance gloss.
[0050] Furthermore, in step S2, the antioxidant is, for example, BASF Irganox 245 hindered phenol antioxidant, which has low volatility and high extraction resistance and can protect spandex from thermal oxidative degradation during production, processing and final use.
[0051] Furthermore, in step S2, the anti-yellowing agent is bis(N,N-dimethylhydrazideamino-4-phenyl)methane (i.e., HN-150 anti-yellowing agent), which has a specific chemical structure and can effectively inhibit nitrogen oxides (NO x ) has good absorption capacity, thus protecting the spandex material from damage by external factors such as light, heat and oxygen, and preventing yellowing.
[0052] Furthermore, in step S2, the matting agent is titanium dioxide, which reduces the light transmittance of the spandex material by absorption, reflection, scattering or adsorption.
[0053] Furthermore, in step S2, the aging temperature is 45-60° C., and the aging time is 20-50 hours. The aging is to further increase the molecular weight of the polyurethane urea solution system to reach a viscosity range suitable for spinning, and to remove bubbles in the solution, so that the properties of the solution system tend to be uniform and stable, which is conducive to the smooth progress of subsequent spinning molding.
[0054] Furthermore, in step S2, the solid content of the spinning solution is 25-35%, and the viscosity at 40°C is 400-800 Pa·s.
[0055] Furthermore, in step S3, the filtration is to remove impurities in the spinning solution to ensure the smooth progress of the spinning process and the quality of the final product. The filtration can use a high-precision filter, such as a rotary filter system (such as RSFgenius), which can effectively block all hard or soft gel particles and ensure the purity of the spinning solution.
[0056] Further, in step S3, the degassing is to remove tiny bubbles in the spinning solution, which may cause the fiber quality to decrease during the spinning process. The degassing equipment can be a negative pressure degassing kettle, a high-speed centrifuge, a rotary scraping degassing machine or an ultrasonic-assisted casting degassing tower, etc. The specific equipment type depends on the viscosity and other characteristics of the spinning solution.
[0057] Furthermore, the specific steps of the dry spinning are as follows:
[0058] F1: The spinning solution after filtration and degassing is quantitatively and evenly pressed into the spinning assembly through a metering pump;
[0059] F2: Under the action of pressure, the spinning solution is squeezed out from the capillaries of the spinneret on the spinning assembly to form a thin stream of filaments and enter the spinning tunnel;
[0060] F3: The spinning tunnel is filled with hot nitrogen or other inert gases, which causes the solvent in the filament stream to evaporate quickly and be carried away by the air. The concentration of the filaments continues to increase until they solidify.
[0061] Furthermore, in the dry spinning step F2, the specification of the spinneret is 1 to 7 holes, the diameter of a single hole is 0.1 to 0.3 mm, and the aspect ratio of the spinneret is (1 to 4):1.
[0062] Furthermore, in the dry spinning step F3, the temperature of the spinning tunnel is set to 220-260° C. to ensure rapid volatilization of the solvent and uniform coagulation of the fibers.
[0063] In the present invention, the false twisting is to perform false twisting on the fibers after passing through the spinning tunnel to enhance the elasticity and stability of the fibers. The winding is to wind the false twisted fibers through a winding device, and the winding speed is controlled to be 300-800 m / min to avoid excessive tension causing fiber breakage or too low tension causing fiber loosening.
[0064] Furthermore, the monofilament fineness of the self-lubricating and stain-resistant spandex is 5-15D.
[0065] Furthermore, in the general formula (I) of the self-lubricating and stain-resistant spandex, a is the degree of polymerization of the siloxane segment formed by the terminal hydroxyl poly (methyl-3,3,3-trifluoropropyl) siloxane, a=3~13; b is the degree of polymerization of the EO segment formed by ethylene oxide, b=2~27; c is the degree of polymerization of the PO segment formed by propylene oxide, c=2~20.
[0066] The present invention has the following beneficial effects:
[0067] (1) The present invention introduces silicon-oxygen bonds into the main chain of spandex and fluorine atoms into the side chain, and realizes the self-lubricating effect and anti-fouling property of spandex through fluorine-siliconization chemical modification, so that no additional lubricant or oil agent is required during the production of spandex, and the surface friction coefficient of spandex fiber can be significantly reduced, thereby achieving significant effects such as good continuity of the spinning production process, high uniformity of the product yarn, excellent unwinding property and no breakage of the yarn during use.
[0068] (2) In the spandex molecules of the present invention, the silicon-oxygen bonds in the main chain have good flexibility and a significant self-lubricating effect; the fluorine atoms are located in the side chains and are enriched on the surface, which is more conducive to improving the dirt resistance. Due to the low surface energy of fluorine and silicon atoms, the spandex products prepared are not easily contaminated by dirt and have good dirt resistance, achieving the function of integrating self-lubrication and dirt resistance, and effectively solving the contradiction between improving the surface lubrication characteristics and dirt resistance in the prior art. The spandex fiber of the present invention has a smooth surface, is skin-friendly and comfortable, and has a wide range of applications.
[0069] (3) The present invention selects fluorinated siliconized modified polyether diol and fluorinated modified amine chain extender as raw materials in the spandex polymerization reaction, and utilizes the outstanding physical and chemical properties of the two to modify the molecular structure of spandex fiber. In the fluorinated siliconized modified polyether diol,
[0070] The low surface free energy of fluorine atoms helps to form a protective layer on the surface of spandex fibers that is difficult to be wetted by water or adhered to by oil stains, thereby improving the spandex's resistance to dirt. The introduction of fluorinated siliconized modified polyether diols can improve the mechanical properties of polyurethane, so that the prepared spandex fibers have higher durability and strength while maintaining good softness and stretchability. Fluorine-modified amine chain extenders are used as chain extenders. The fluorine atoms in them also have low surface energy and hydrophobic and oleophobic properties. They are introduced into the polyurethane molecular chain during the chain extension process, further enhancing the spandex's resistance to dirt.
[0071] (4) By reasonably regulating the proportion of EO and PO segments in the fluorosilicone modified polyether, the hydrophilicity can be flexibly adjusted, the product has good moisture absorption and perspiration effect, is conducive to the development of differentiated products, is suitable for a variety of application scenarios, and has great market potential. Specifically, the polyurethane structure prepared by the fluorosilicone modified polyether diol with EO segment as the main segment has good hydrophilicity, but low mechanical strength; the polyurethane structure prepared by the fluorosilicone modified polyether diol with PO segment as the main segment has high mechanical strength, but weak hydrophilicity. By reasonably regulating the proportion of the two segments, various products with different characteristics can be made, and the scope of application is relatively wide. For example, in the fields of sanitary materials, etc., hydrophilicity and moisture absorption and perspiration are required, and spandex fibers with a high proportion of EO can be selected; the outer fabric of outdoor sportswear requires good mechanical strength and good water resistance, and spandex fibers with a high proportion of PO can be selected. The present invention can flexibly design spandex products that meet different performance requirements by finely regulating various parameters in the fluorosilicone modification process, such as the fluorine-silicone ratio, the EO / PO segment ratio, etc., to achieve customized and personalized production of products and meet the diversified needs of the market.
[0072] (5) Since no spinning oil or lubricant is required in the spinning production process of the present invention, the spandex production process is simplified, which is beneficial to reducing costs and increasing efficiency.
[0073] (6) The modified spandex fiber has better skin affinity and air permeability. In addition, the low resistance brought by its self-lubricating property makes the textiles made from it more comfortable to wear without feeling restrained. It is especially suitable for high-demand fields such as sportswear and underwear, which improves the wearing experience of consumers. The spandex products applied for in the present invention can break the traditional application restrictions by virtue of their excellent comprehensive properties such as self-lubrication, stain resistance, moisture absorption and perspiration wicking, and are widely used in outdoor sports equipment, medical care products, automotive interiors, home textiles and other fields, bringing technological innovation and industrial upgrading to these industry products. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 This is an infrared spectrum of the self-lubricating and stain-resistant spandex product prepared in Example 1 of the present invention.
[0075] Figure 2 Schematic diagram of the reaction equation of the self-lubricating and dirt-resistant spandex of the present invention, wherein R1 is ; R2 is . DETAILED DESCRIPTION
[0076] The present invention is further described below in conjunction with the examples, but the present invention is not limited to the following examples. For the sake of comparison, the spinning process of the following examples all uses a 7-hole spinneret, with a single hole diameter of 0.3 mm, an aspect ratio of 4:1, and a controlled winding speed of 500 m / min to spin a spandex product with a fineness specification of 100D.
[0077] Example 1
[0078] The number average molecular weight of the self-lubricating and anti-fouling spandex is 30000-50000 g / mol, the main chain of the molecular structure contains a silicon-oxygen bond, and the side chain contains a fluorine atom. The molecular structure of the self-lubricating and anti-fouling spandex comprises the following general formula (I):
[0079]
[0080] Among them, R1 is ;
[0081] R2 is ;
[0082] a, b, c, x and y are all positive integers;
[0083] a=3~13, b=2~27, c=2~20;
[0084] x is the degree of polymerization of the soft segment, x=57~108;
[0085] y is the degree of polymerization of the hard segment, y=33~78.
[0086] Preparation method:
[0087] (1) Preparation of fluorinated siliconized modified polyether diol with a number average molecular weight of 1000 g / mol, wherein the mass ratio of EO segment to PO segment is 0.5:1. The fluorinated siliconized modified polyether diol is prepared by reacting poly(methyl-3,3,3-trifluoropropyl)siloxane with a number average molecular weight of 500 g / mol as an initiator with ethylene oxide and propylene oxide at a temperature of 50 to 70°C with Lewis acid as a catalyst for 2 to 5 hours through a ring-opening reaction.
[0088] (2) The preparation steps of self-lubricating and stain-resistant spandex are as follows:
[0089] Step S1: 73.66 kg of 4,4'-diphenylmethane diisocyanate and 196.22 kg of fluorinated siliconized modified polyether diol are subjected to a prepolymerization reaction at 50° C. for 120 min at a molar ratio of 1.5:1 to form an isocyanate-terminated fluorinated siliconized modified polyurethane prepolymer, and 272.26 kg of N,N'-dimethylacetamide is added and dissolved to prepare a fluorinated siliconized modified polyurethane prepolymer solution;
[0090] Step S2: adding a mixed amine solution consisting of 19.0 kg of fluorine-modified amine chain extender, 0.687 kg of 1,2-propylenediamine, 1.128 kg of diethylamine, and 267.51 kg of N,N'-dimethylacetamide (wherein the molar ratio of the fluorine-modified amine chain extender, 1,2-propylenediamine, and diethylamine is 5.4:0.6:1) to the fluorine-siliconized modified prepolymer solution, and performing a chain extension reaction at 30°C for 80 min to form a fluorine-siliconized modified polyurethane urea solution, adding 2 kg of BASF Irganox245 antioxidant, 2 kg of TiO2 matting agent, and 1 kg of HN-150 anti-yellowing agent, and stirring at 45°C for 20 h to prepare a spinning solution, wherein the spinning solution has a solid content of 35% and a viscosity of 400 Pa·s (40°C);
[0091] Step S3: filtering and degassing the spinning solution and then performing dry spinning at a spinning tunnel temperature of 260° C., and then false twisting and winding to obtain self-lubricating and dirt-resistant spandex.
[0092] Figure 1 This is the infrared spectrum of the self-lubricating and anti-fouling spandex prepared in Example 1. Among them, 1259 cm -1 、1299 cm -1 The -CF3 peak is at 1026 cm -1 The -Si-O- bond peak is at 801 cm -1 The -Si-C-bond peak is at 1108 cm -1 The ether bond (-O-) peak at 47° becomes broader due to the effect of fluorine atoms.
[0093] Example 2
[0094] The number average molecular weight of the self-lubricating and anti-fouling spandex is 30000-50000 g / mol, the main chain of the molecular structure contains a silicon-oxygen bond, and the side chain contains a fluorine atom. The molecular structure of the self-lubricating and anti-fouling spandex comprises the following general formula (I):
[0095]
[0096] Among them, R1 is ;
[0097] R2 is ;
[0098] a, b, c, x and y are all positive integers;
[0099] a=3~13, b=2~27, c=2~20;
[0100] x is the degree of polymerization of the soft segment, x=57~108;
[0101] y is the degree of polymerization of the hard segment, y=33~78.
[0102] Preparation method:
[0103] (1) A fluorinated siliconized modified polyether diether with a number average molecular weight of 2000 g / mol was prepared, wherein the mass ratio of the EO segment to the PO segment was 2:1; the fluorinated siliconized modified polyether diether was prepared by reacting an initiator poly(methyl-3,3,3-trifluoropropyl)siloxane with a number average molecular weight of 1000 g / mol with ethylene oxide and propylene oxide at a temperature of 50 to 70°C and using a Lewis acid as a catalyst, through a ring-opening reaction for 2 to 5 hours.
[0104] (2) The preparation steps of self-lubricating and stain-resistant spandex are as follows:
[0105] Step S1: 53.57 kg of 4,4'-diphenylmethane diisocyanate and 214.06 kg of fluorinated siliconized modified polyether diol are subjected to a prepolymerization reaction at 65° C. for 60 min at a molar ratio of 2:1 to form an isocyanate-terminated fluorinated siliconized modified polyurethane prepolymer, and 336.42 kg of N,N'-dimethylacetamide is added and dissolved to prepare a fluorinated siliconized modified polyurethane prepolymer solution;
[0106] Step S2: Add a mixed amine solution consisting of 21.34 kg of fluorine-modified amine chain extender, 0.770 kg of 1,2-propylenediamine, 0.950 kg of diethylamine, and 281.20 kg of N,N'-dimethylacetamide (wherein the molar ratio of the fluorine-modified amine chain extender, 1,2-propylenediamine, and diethylamine is 7.2:0.8:1) to the fluorine-siliconized modified prepolymer solution, and carry out a chain extension reaction at 40°C for 60 minutes to form a fluorine-siliconized modified polyurethane urea solution, add 2 kg of BASF Irganox245 antioxidant, 2 kg of TiO2 matting agent, and 1 kg of HN-150 anti-yellowing agent, and stir at 50°C for 35 hours to mature to prepare a spinning solution, wherein the spinning solution has a solid content of 32% and a viscosity of 497.6 Pa·s (40°C).
[0107] S3: The spinning solution is filtered and degassed before dry spinning at a spinning tunnel temperature of 245°C, and then false twisting and winding are performed to obtain self-lubricating, dirt-resistant spandex.
[0108] Example 3
[0109] The number average molecular weight of the self-lubricating and anti-fouling spandex is 30000-50000 g / mol, the main chain of the molecular structure contains a silicon-oxygen bond, and the side chain contains a fluorine atom. The molecular structure of the self-lubricating and anti-fouling spandex comprises the following general formula (I):
[0110]
[0111] Among them, R1 is ;
[0112] R2 is ;
[0113] a, b, c, x and y are all positive integers;
[0114] a=3~13, b=2~27, c=2~20;
[0115] x is the degree of polymerization of the soft segment, x=57~108;
[0116] y is the degree of polymerization of the hard segment, y=33~78.
[0117] Preparation method:
[0118] (1) Preparation of fluorinated siliconized modified polyether diol with a number average molecular weight of 3000 g / mol, wherein the mass ratio of EO segment to PO segment is 1:1. The fluorinated siliconized modified polyether diol is prepared by reacting poly(methyl-3,3,3-trifluoropropyl)siloxane with a number average molecular weight of 1500 g / mol as an initiator with ethylene oxide and propylene oxide at a temperature of 50 to 70°C with Lewis acid as a catalyst for 2 to 5 hours through a ring-opening reaction.
[0119] (2) The preparation steps of self-lubricating and stain-resistant spandex are as follows:
[0120] Step S1: 45.98 kg of 4,4'-diphenylmethane diisocyanate and 220.46 kg of fluorinated siliconized modified polyether diol are subjected to a prepolymerization reaction at 70° C. for 100 min at a molar ratio of 2.5:1 to form an isocyanate-terminated fluorinated siliconized modified polyurethane prepolymer, and 456.99 kg of N,N'-dimethylacetamide is added to dissolve to prepare a fluorinated siliconized modified polyurethane prepolymer solution.
[0121] Step S2: Add a mixed amine solution consisting of 22.55 kg of fluorine-modified amine chain extender, 0.815 kg of 1,2-propylenediamine, 0.893 kg of diethylamine, and 290.38 kg of N,N'-dimethylacetamide (wherein the molar ratio of the fluorine-modified amine chain extender, 1,2-propylenediamine, and diethylamine is 8.1:0.9:1) to the fluorine-siliconized modified prepolymer solution, and carry out a chain extension reaction at 45°C for 50 minutes to form a fluorine-siliconized modified polyurethane urea solution, add 2 kg of BASF Irganox245 antioxidant, 2 kg of TiO2 matting agent, and 1 kg of HN-150 anti-yellowing agent, and stir at 55°C for 40 hours to mature to prepare a spinning solution, wherein the spinning solution has a solid content of 28% and a viscosity of 610.8 Pa·s (40°C).
[0122] Step S3: filtering and degassing the spinning solution, and then performing dry spinning at a spinning tunnel temperature of 230° C., and then false twisting and winding to obtain self-lubricating and dirt-resistant spandex.
[0123] Example 4
[0124] The number average molecular weight of the self-lubricating and anti-fouling spandex is 30000-50000 g / mol, the main chain of the molecular structure contains a silicon-oxygen bond, and the side chain contains a fluorine atom. The molecular structure of the self-lubricating and anti-fouling spandex comprises the following general formula (I):
[0125]
[0126] Among them, R1 is ;
[0127] R2 is ;
[0128] a, b, c, x and y are all positive integers;
[0129] a=3~13, b=2~27, c=2~20;
[0130] x is the degree of polymerization of the soft segment, x=57~108;
[0131] y is the degree of polymerization of the hard segment, y=33~78.
[0132] Preparation method:
[0133] (1) Preparation of fluorinated siliconized modified polyether diol with a number average molecular weight of 4000 g / mol, wherein the mass ratio of EO segment to PO segment is 1:1. The fluorinated siliconized modified polyether diol is prepared by reacting poly(methyl-3,3,3-trifluoropropyl)siloxane with a number average molecular weight of 2000 g / mol as an initiator with ethylene oxide and propylene oxide at a temperature of 50 to 70°C with Lewis acid as a catalyst for 2 to 5 hours through a ring-opening reaction.
[0134] (2) The preparation steps of self-lubricating and stain-resistant spandex are as follows:
[0135] Step S1: 41.96 kg of 4,4'-diphenylmethane diisocyanate and 223.57 kg of fluorinated siliconized modified polyether diol are prepolymerized at 80° C. for 120 min in a molar ratio of 3:1 to form an isocyanate-terminated fluorinated siliconized modified polyurethane prepolymer, and 582.05 kg of N,N'-dimethylacetamide is added to dissolve to prepare a fluorinated siliconized modified polyurethane prepolymer solution.
[0136] Step S2: Add a mixed amine solution consisting of 23.61 kg of fluorine-modified amine chain extender, 0.853 kg of 1,2-propylenediamine, 0.702 kg of diethylamine, and 289.88 kg of N,N'-dimethylacetamide (wherein the molar ratio of the fluorine-modified amine chain extender, 1,2-propylenediamine, and diethylamine is 10.8:1.2:1) to the fluorine-siliconized modified prepolymer solution, and carry out a chain extension reaction at 50°C for 40 minutes to form a fluorine-siliconized modified polyurethane urea solution, add 2 kg of BASF Irganox245 antioxidant, 2 kg of TiO2 matting agent, and 1 kg of HN-150 anti-yellowing agent, and stir at 60°C for 50 hours to mature to prepare a spinning solution, wherein the spinning solution has a solid content of 25% and a viscosity of 800 Pa·s (40°C).
[0137] Step S3: filtering and degassing the spinning solution, and then performing dry spinning at a spinning tunnel temperature of 220° C., and then false twisting and winding to obtain self-lubricating and dirt-resistant spandex.
[0138] Comparative Example 1
[0139] The difference between this comparative example 1 and example 2 is that in step S2, ordinary ethylenediamine chain extender is used to replace the fluorine-modified amine chain extender in example 2, and the other implementation conditions are the same.
[0140] Comparative Example 2
[0141] The difference between this comparative example 2 and example 2 is that ordinary polytetramethylene ether glycol (PTMEG) with a molecular weight of 2000 g / mol ( ) replaces the fluorinated siliconized modified polyether diol in Example 2, and in step S2, ordinary ethylenediamine chain extender is used to replace the fluorinated modified amine chain extender in Example 2, and the other implementation conditions are the same.
[0142] Comparative Example 3
[0143] The difference between Comparative Example 3 and Comparative Example 1 is that only 5 kg of magnesium stearate solid lubricant is added as an auxiliary material in step S2.
[0144] Comparative Example 4
[0145] The difference between Comparative Example 4 and Comparative Example 1 is that only 5 kg of dimethyl silicone oil liquid lubricant is added as an auxiliary material in step S2.
[0146] The spandex product testing methods of the embodiments and comparative examples are as follows:
[0147] (1) Friction coefficient test method: The Y151 fiber friction coefficient tester is used, based on the capstan method principle. During the test, the two ends of the spandex are clamped with tension clamps of the same weight m, suspended on a metal roller, and then a force F is applied under the tension clamp. When the F value is equal to or slightly greater than the static friction force of the tested fiber package on the fiber roller, the suspension loses balance and slips, and the static friction force is obtained. If the fiber roller is rotated counterclockwise at this time, and the F value is adjusted to regain the balance of the suspension, the F force value is the dynamic friction force at this speed, and the friction coefficient is calculated by the following formula.
[0148] μ=0.737[lg f 0-lg( f 0-F)]
[0149] In the formula f 0 is the pre-tension and F is the torsion balance reading.
[0150] (2) Mechanical properties test method: The test was carried out in accordance with the relevant standard procedures of the spandex industry, including "FZ / T 50005-2013 Test method for spandex yarn density", "FZ / T 50006-2013 Test method for spandex yarn tensile properties", and "FZ / T 50007-2012 Test method for spandex yarn elasticity". In order to facilitate statistical comparison, the average value of the sum of the discrete coefficients of the individual mechanical properties of each test sample was recorded as the unevenness rate.
[0151] (3) Test method for stain resistance: Prepare stains according to the method described in GB / T 30159.1-2013 Testing and evaluation of stain resistance of textiles Part 1: Stain resistance. The liquid stains are high-salt dilute fermented soy sauce (dark soy sauce) that complies with GB18186-2000. The solid stains have a particle size of ≤60 μm, and high-pigment carbon black complies with GB / T 7044-2003, with the specification of C111 powder. Mix and prepare according to the proportions in Table 1.
[0152] Table 1. Solid dirt preparation table for dirt resistance test
[0153]
[0154] During the test, weigh and record about 5g of spandex fiber sample, put it into 200mL of liquid dirt or 300g of solid dirt, ensure that the sample is completely immersed in the dirt, stir it with a stirrer at 200rpm for 10min, then take it out with tweezers and leave it in the air for 2min to test the weight of the fiber containing residual dirt, and calculate the ratio of the residual dirt weight to the original weight of the fiber sample.
[0155] (4) Unwinding test method: Take the outer, middle and inner layers of the spandex product, use a homemade unwinding device to test the spandex tension during the unwinding process, and calculate the average value as the result. The unwinding speed is 0.5m / s. The smaller the unwinding tension value, the smaller the adhesion between the yarns during unwinding, and the better the unwinding performance.
[0156] The spandex product data in each embodiment and comparative example measured by the above detection method are shown in Table 2 below:
[0157] Table 2 Test results of embodiments and comparative examples
[0158]
[0159] It can be seen from the test results of the above embodiments and comparative examples that the spandex product made by the technology described in the present invention has a significantly reduced friction coefficient, a significantly reduced amount of liquid or solid dirt residue, and has higher mechanical strength, elongation at break, elastic recovery rate, good yarn uniformity, and strong comprehensive mechanical properties.
[0160] It can be seen from the test results of Examples 1 to 4 above that as the molecular weight of the poly(methyl-3,3,3-trifluoropropyl)siloxane initiator in the fluorosilicone modified polyether increases, the dirt resistance and elongation at break gradually improve, but the breaking strength decreases. In actual application, it is necessary to reasonably select the type and ratio of raw materials in the formula based on the application scenario.
[0161] By comparing Comparative Example 1 and Example 2, it can be seen that since only fluorinated siliconized modified polyether diol is used in Comparative Example 1, and fluorinated modified amine chain extender is not used, only the soft segment of the formed molecular structure contains fluorine, and the hard segment does not contain fluorine. Therefore, the anti-fouling performance is weaker than that of Example 2, which proves that the simultaneous use of fluorinated siliconized polyether diol and fluorinated modified amine chain extender can further effectively enhance the anti-fouling effect and reduce the surface friction coefficient.
[0162] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.
Claims
1. A self-lubricating and dirt-resistant spandex, characterized in that: The number average molecular weight of the self-lubricating and anti-fouling spandex is 30,000-50,000 g / mol, the main chain of the molecular structure contains a silicon-oxygen bond, and the side chain contains a fluorine atom. The molecular structure of the self-lubricating and anti-fouling spandex comprises the following general formula (I): ; Formula (I) Among them, R1 is ; R2 is ; a, b, c, x and y are all positive integers; a=3~13, b=2~27, c=2~20; x is the degree of polymerization of the soft segment, x=57~108; y is the degree of polymerization of the hard segment, y=33~78.
2. A method for preparing the self-lubricating and stain-resistant spandex according to claim 1, characterized in that: The following steps are involved: Step S1 Prepolymerization reaction: 4,4'-diphenylmethane diisocyanate and fluorinated siliconized modified polyether diol are subjected to prepolymerization reaction to form isocyanate terminated fluorinated siliconized modified polyurethane prepolymer, and N,N'-dimethylacetamide is added to dissolve the prepolymer to prepare a fluorinated siliconized modified polyurethane prepolymer solution; Step S2 Chain extension reaction: Adding a mixed amine solution consisting of a fluorine-modified amine chain extender, 1,2-propylenediamine, diethylamine, and N,N'-dimethylacetamide to the fluorine-siliconized modified polyurethane prepolymer solution to carry out a chain extension reaction to form a fluorine-siliconized modified polyurethane urea solution, and preparing a spinning solution by adding auxiliary materials, stirring, and aging; Step S3 Spinning: The spinning solution is filtered and degassed before dry spinning, and then false twisted and wound to obtain self-lubricating and dirt-resistant spandex without oiling. Wherein, in step S1, the fluorosilicified modified polyether diol is prepared by ring-opening reaction with ethylene oxide and propylene oxide in sequence using terminal hydroxyl poly (methyl-3,3,3-trifluoropropyl) siloxane with a number average molecular weight of 500-2000 g / mol as an initiator, wherein the mass ratio of EO segment to PO segment is (0.5-2): 1, and the reaction equation is as follows: Where a, b, and c are the polymerization degrees of the siloxane segment, EO segment, and PO segment, respectively; a=3~13, b=2~27, c=2~20; In step S2, the fluorine-modified amine chain extender is prepared by Michael addition reaction of ethylenediamine and trifluoroethyl acrylate, as shown below: 。 3. The preparation method according to claim 2, characterized in that: In step S1, the number average molecular weight of the fluorinated siliconized modified polyether diol is 1000-4000 g / mol.
4. The preparation method according to claim 2, characterized in that: In step S1, the molar ratio of the 4,4'-diphenylmethane diisocyanate to the fluorinated siliconized modified polyether diol is (1.5-3):
1.
5. The preparation method according to claim 2, characterized in that: In step S1, the prepolymerization reaction temperature is 50-80°C, and the reaction time is 60-120 min.
6. The preparation method according to claim 2, characterized in that: In step S2, the molar ratio of the fluorine-modified amine chain extender, 1,2-propylenediamine, and diethylamine is (5.4-10.8): (0.6-1.2):
1.
7. The preparation method according to claim 2, characterized in that: In step S2, the temperature of the chain extension reaction is 30-50° C., and the reaction time is 40 min-80 min.
8. The preparation method according to claim 2, characterized in that: In step S2, the aging temperature is 45-60°C, and the aging time is 20-50 hours.
9. The preparation method according to claim 2, characterized in that: In step S2, the solid content of the spinning solution is 25-35%, and the viscosity at 40°C is 400-800 Pa·s.
Citation Information
Patent Citations
Elastic fibers containing anti-sticking additives
CN102362020B
A method for preparing spandex for diapers
CN108221076B
A modified spandex fiber material and its preparation method
CN111155313B
A method for preparing nano-modified easy-wrap spandex
CN113005559B
Spandex with improved backing-off property and creep property for paper diaper and production method thereof
CN107502978A